Occurrence and Recurrence of Seizures and Related Factors in Patients With Tramadol Ingestion - Okazi, Arash; Taghaddosinejad, Fakhreddin; Mazrouei, Najmeh; Forouzesh, Mehdi; Barzegar, Abdolrazagh; Fallah, Fardin (International Journal of Medical Toxicology and Forensic Medicine, 2018)
Background: Rate of tramadol poisoning and seizure and its complications is high in Iran. We investigated the occurrence and recurrence of tramadol-induced seizures and related factors in patients with tramadol poisoning. Methods: This was a descriptive longitudinal study conducted in a poisoning referral hospital in Tehran, Iran. During April to June 2017, adult patients (≥16 years) with tramadol ingestion and poisoning admitted to hospital were selected by convenience sampling method. We studied the rate of seizure occurrence and recurrence among them. Also, the association between seizure occurrence and recurrence and patients’ demographic characteristics and poisoning-related factors were investigated. Data were analyzed by SPSS 16 and significant level was set at <0.05. Results: In total, 250 patients participated in the study. Their mean age was 26.39 years and 214 (85.6%) of them were male. Of all, 159 (63.6%) were single, 106 (42.4%) were unemployed and 24 (9.6%) were students. Main reason of tramadol consumption was suicide. Co-administration of drugs was reported in 83 (33.2%) cases. Incidence of seizure occurrence and recurrence were 31% and 38.5%, respectively. There was no statistically significant relationship between the occurrence and recurrence of seizures and patients’ age, gender, marital status, occupation, reason for tramadol consumption, co-administration of drugs and naloxone administration. Probability of seizure occurrence and recurrence raised with increased tramadol dose (P<0.001 and P<0.01, respectively). Seizure recurrence led to longer hospital stay (P<0.001). Conclusion: Rate of the occurrence and recurrence of tramadol-induced seizure seems clinically significant, but the prognosis is generally good in cases with seizure. Greater ingested dose and late hospital admission were associated with higher probability of seizure occurrence and recurrence. Further studies are required to investigate the risk factors of tramadol-induced seizure.